The Consumption of Traditional Medicine by Type 2 Diabetes Mellitus Patients at the Public Health Center of Panjatan in the Regency of Kulon Progo as a Case Study - Enuk Endah Sunarto; Mora Claramita; M Robikhul Ikhsan (Faculty of Medicine, Public Health, and Nursing, 2019)
Background: The consumption of traditional medicine is very much done in the society including by type 2 diabetes mellitus patients.Purpose: This study is purposed to understand the reasons of type 2 diabetes mellitus patients at the Public Health Center of Panjatan in the Regency of Kulon Progo in consuming traditional medicine and their knowledge about type 2 diabetes mellitus.Method: This study is a qualitative research with case study approach. The data is obtained through focus group discussion involved 56 type 2 diabetes mellitus patients. The data is analyzed by qualitative analysis techniques from Miles and Huberman.Results: The reasons of type 2 diabetes mellitus patients in consuming traditional medicine, i.e. (1) they are following friends or relatives who has consumed traditional medicine that is considered successful, or (2) they are not believing in the medical doctor's treatment. The economic and distance factors are not their consideration. The type 2 diabetes mellitus patients who have consumed traditional medicine but have now stopped have the following reasons: (1) they are asked to stop in consuming traditional medicine by medical doctors; (2) they said that it is not practical how to mix traditional medicine so that they become lazy to consume traditional medicine; or (3) the mixing of traditional medicine is easily depleted. In addition, from this study also known that some type 2 diabetes mellitus patients understand very well about type 2 diabetes mellitus disease suffered, some others do not have enough knowledge about type 2 diabetes mellitus.Conclusion: The type 2 diabetes mellitus patients in consuming traditional medicine are due to various factors, i.e. the trust of medical doctors, following friends or relatives as well as sufficient knowledge about the effects of traditional medicine. This study also founded that generally all type 2 diabetes mellitus patients understand the disease they suffered well.